The Confucian Middle Way. Can it be Walked Along? - Poškaitė, Loreta (Acta Orientalia Vilnensia, 2001)
The article deals with the concept and value of the Middle way in Confucianism. The purpose of this article is to reveal not only its ethical and social,but the ontological and religious meaning as well. For this purpose three main intercrossing functional aspects of the Middle way are singled out: 1) qualitative–formal (according to which the Middle way is expressed as the moderation), 2) quantitative–humanistical (the Middle way as the reciprosal change and support), 3) depthfull–universal (as the unity and identity of the human and Heaven, or the cosmos). Close attention here is given to the fact, that the Chinese word zhong means not only middle or mean (as it is usually translated into West European languages), but, primarily the centre or centrality. Due to this, the Middle way may be conceived not only as the simple balance between the extremes or the search for the compromises, but as the concentration of many perspectives, the open and non-localized centre, which is based on the ordinary experience and thus not possible for the dogmatization, sistematization and rendering. Because of this, the pursuit and maintenance of the Middle way becomes at once too intimate as well as a hardly realizable task.